Peran Komunikasi Pemasaran terhadap UMKM di Kecamatan Medan Area - Erwan Effendi; Zakaria Zakaria; Rico Rinaldi; Muhammad Andi Harahap (Journal on Education, 2023)
This study aims to analyze the extent of the role of marketing communications for Micro, Small and Medium Enterprises (MSMEs). The focus of the study in this study consists of two things, namely the role of marketing communications, supporting factors for MSMEs, and efforts to develop MSMEs through technology. The research method used is qualitative based on descriptive studies. Data collection techniques used are observation, interviews, and documentation studies. The data obtained were then analyzed using the Miles and Huberman technique. The results of the study explain that marketing communications have a very important role in improving community SMEs. Because with good marketing communication, MSME actors can promote their products in many ways, such as through social media. Especially now it's very easy to sell products on social media.